IDH2 mutations define a unique subtype of breast cancer with altered nuclear polarity - Chiang, Sarah; Deimling, Andreas von (Cancer research, 2016)
Solid papillary carcinoma with reverse polarity (SPCRP) is a rare breast cancer subtype with an obscure etiology. In this study, we sought to describe its unique histopathologic features and to identify the genetic alterations that underpin SPCRP using massively parallel whole-exome and targeted sequencing. The morphologic and immunohistochemical features of SPCRP support the invasive nature of this subtype. Ten of 13 (77%) SPCRPs harbored hotspot mutations at R172 of the isocitrate dehydrogenase IDH2, of which 8 of 10 displayed concurrent pathogenic mutations affecting PIK3CA or PIK3R1. One of the IDH2 wild-type SPCRPs harbored a TET2 Q548* truncating mutation coupled with a PIK3CA H1047R hotspot mutation. Functional studies demonstrated that IDH2 and PIK3CA hotspot mutations are likely drivers of SPCRP, resulting in its reversed nuclear polarization phenotype. Our results offer a molecular definition of SPCRP as a distinct breast cancer subtype. Concurrent IDH2 and PIK3CA mutations may help diagnose SPCRP and possibly direct effective treatment. Cancer Res; 76(24); 7118-29. ©2016 AACR.
Gesehen am 30.04.2020